SYNERGISTIC ON AUXIN AND CYTOKININ 1 positively regulates growth and attenuates soil pathogen resistance - Hurný, Andrej; Cuesta, Candela; Cavallari, Nicola; Ötvös, Krisztina; Duclercq, Jerome; Dokládal, Ladislav; Montesinos, Juan Carlos; Gallemí, Marçal; Semerádová, Hana; Rauter, Thomas; Stenzel, Irene; Persiau, Geert; et al. (Nature communications, 2020)
Plants as non-mobile organisms constantly integrate varying environmental signals to flexibly adapt their growth and development. Local fluctuations in water and nutrient availability, sudden changes in temperature or other abiotic and biotic stresses can trigger changes in the growth of plant organs. Multiple mutually interconnected hormonal signaling cascades act as essential endogenous translators of these exogenous signals in the adaptive responses of plants. Although the molecular backbones of hormone transduction pathways have been identified, the mechanisms underlying their interactions are largely unknown. Here, using genome wide transcriptome profiling we identify an auxin and cytokinin cross-talk component; SYNERGISTIC ON AUXIN AND CYTOKININ 1 (SYAC1), whose expression in roots is strictly dependent on both of these hormonal pathways. We show that SYAC1 is a regulator of secretory pathway, whose enhanced activity interferes with deposition of cell wall components and can fine-tune organ growth and sensitivity to soil pathogens.
Keywords: Plant Roots; Soil; Cell Wall; Disease Resistance; vezikulární transportní proteiny; Gene Expression Profiling; půda; Gene Expression Regulation, Plant; Secretory Pathway; Cytokinins; Endosomes; cytokininy; kořeny rostlin; Plant Growth Regulators; Indoleacetic Acids; proteiny huseníčku; Arabidopsis Proteins; buněčná stěna; transkriptom; Golgi Apparatus; Plants, Genetically Modified; geneticky modifikované rostliny; endozomy; stanovení celkové genové exprese; Golgiho aparát; Vesicular Transport Proteins; regulace genové exprese u rostlin; sekreční dráha; Arabidopsis; odolnost vůči nemocem; Membrane Proteins; regulátory růstu rostlin; Transcriptome; membránové proteiny; Plasmodiophorida; kyseliny indoloctové